Kinetic parameters of lactic acid bacterial isolated from fermented milk “Suero Costeño” (2018)
ABSTRACT: The isolation of bacteria from artisanal dairy products has increased in different countries, it has reported special technological properties, responsible for giving to dairy products unique characteristics. The kinetic parameters of native microorganisms are important for biotechnological scaling. This research, to evaluated the kinetics of bacterial growth under optimal conditions of lactic acid bacterial isolated from artisanal fermented milk “Suero Costeño” Lactobacillus plantarum (Lp), Streptococcus infantarius (Si)and Lactococcus lactis (Ll), identified by 16S rRNA. There were fast rate acidificationof Si and Ll as a typical dairy starter culture. Lp showed a slowly rate acidification and highest pH resistance. It is necessary a pH control between 5,3 and 5,7 in order to obtain higher consume of substrate and yield biomass. Si and Ll can be used as primary cultures in fermentations as a result of their rapid acidification and Lp as an adjunct culture through the slow acid production.